Dampak Lingkungan dan Disiplin Belajar terhadap Prestasi Siswa SMP di Sekolah Minggu Buddha Maitreya Palembang - Jordy Steffanus (Institut Nalanda, 2025)
This research aims first to determine the partial relationship between the learning environment on learning outcomes and learning discipline on learning outcomes. The second is to determine the simultaneous relationship between the learning environment and learning discipline on student learning outcomes at SMB Maitreya Middle School in Palembang City. This research uses quantitative methods. The sample taken in the study was 139 people using a saturated sampling technique, which means a sampling technique that uses all members of the population as samples. The data collection technique in this research was by distributing questionnaires via Google forms online to 139 students in various SMBs in Palembang City. The results of research data analysis show that the regression value of 0.867 indicates a significant relationship between the learning environment, learning discipline and learning outcomes. The Fcount value of 25.8 is greater than Ftable (3.09), this means that there is a significant joint/simultaneous influence between the learning environment, learning discipline on student learning outcomes at SMB Maitreya Palembang Middle School. The coefficient of determination or R Square value for the three variables is 75.2%. Meanwhile, the remaining 24.8% is influenced by other variables.